The Relationships between Current Ratio, Firm Age, Good Corporate Governance, and Corporate Social Responsibility: The Moderating Effects of Firm Size - Kumba Digdowiseiso (Shirkah: Journal of Economics and Business, 2023)
Few studies have explored how firm size moderates the effect of the current ratio, firm age, and good corporate governance on corporate social responsibility. This research examined the effect of current ratio, firm age, and good corporate governance on corporate social responsibility. It explored the moderating effects of firm size on the relationships between current ratio, firm age, and good corporate governance on corporate social responsibility among mining sector companies listed on the Indonesia Stock Exchange from 2017 to 2021. Purposive sampling was used to select 17 different mining firms that met the study's criteria. By applying a moderated regression analysis, the results indicated a negative and statistically insignificant relationship between the current ratio and corporate social responsibility. Corporate social responsibility was positively affected by the maturity of the company and by its commitment to ethical business practices. Meanwhile, there was an inverse relationship between firm size and corporate social responsibility. Furthermore, firm size did not affect the relationship between the current ratio and corporate social responsibility, nor the relationship between firm age and corporate social responsibility. This study revealed that firm size weakened the link between good corporate governance and corporate social responsibility.